Remoción de níquel, cadmio y zinc del agua, utilizando clinoptilolita heulandita - Pavón Silva, Thelma B.; Campos, Eduardo; Teresa Olguín, María (CIENCIA ergo-sum; Vol. 7 Núm. 3 (2000): CIENCIA ergo-sum (noviembre 2000-febrero 2001), 2015)
-